Partial knowledge restrictions on the two-stage threshold model of choice - Paola Manzini; Marco Mariotti; Christopher J. Tyson (Queen Mary University of London, School of Economics and Finance, 2016)
In the context of the two-stage threshold model of decision making, with the agent's choices determined by the interaction of three "structural variables," we study the restrictions on behavior that arise when one or more variables are exogenously known. Our results supply necessary and sufficient conditions for consistency with the model for all possible states of partial knowledge, and for both single- and multi-valued choice functions.
Keywords: D10; D30; 330; Attention; Revealed preference; Salience; Satisficing